The leap of the school curriculum in contemporaneity - Lopes Da Barra, Valdeniza (2021)
The text analyses the school curriculum in three moments. First, it promotes dialogue with Brazilian scholars who openly discuss the current school curriculum in Brazilian reality. Then, it identifies some roots of the situation that induces the leap in the logic that guides the curriculum, rather than the specificity of knowledge and, from a certain point, provided in various contemporary sociocultural issues. For this purpose, the article draws on theoretical perspectives that thematize the paradigm of historicity, post-modernity, and the present “long time”. This analysis indicates the emergence and challenges of themes that have been erased, remembered, reformulated, and inaugurated (ethnic/racial conflicts, environment, sexuality, among others), establishing new relationships between past, present, and future. Finally, it shows the leap in the school curriculum in two structural documents that regulate the theme in contemporary Brazil.